2006
DOI: 10.1111/j.1369-1600.2006.00045.x
|View full text |Cite
|
Sign up to set email alerts
|

GENETIC STUDY: Association between the BclI glucocorticoid receptor polymorphism and smoking in a sample of patients with obstructive airway disease

Abstract: Glucocorticoids seem to mediate the effect of stimulant drugs such as nicotine. Several studies have pointed to an association between the BclI polymorphism in the glucocorticoid receptor gene and increased glucocorticoid effects. We analysed the association of smoking behaviour and the BclI polymorphism using a case-control design within the framework of a larger pharmacogenetic study. A total of 327 Caucasian patients with asthma or chronic obstructive pulmonary disease from 39 German general practices gave … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 30 publications
0
5
1
Order By: Relevance
“…In contrast to previous research (e.g., Rogausch et al, 2007;Tang et al, 2015), genetic variation within the NR3C1 and CRHR1…”
Section: Sex-specific Pleiotropy In Nr3c2contrasting
confidence: 98%
See 1 more Smart Citation
“…In contrast to previous research (e.g., Rogausch et al, 2007;Tang et al, 2015), genetic variation within the NR3C1 and CRHR1…”
Section: Sex-specific Pleiotropy In Nr3c2contrasting
confidence: 98%
“…Gillespie, Phifer, Bradley, & Ressler, 2009), only a handful of studies have examined associations with smoking behavior. For example, Rogausch, Kochen, Meineke, and Hennig (2007) found that G allele carriers at rs41423247 of NR3C1 were more likely to become smokers and had significantly higher daily cigarette consumption than C homozygotes. Other SNPs within NR3C2, FKBP5, and CRHR1 have also been examined in relation to smoking outcomes (dos Santos et al, 2012;Jensen et al, 2015;Koopmann et al, 2016;Rovaris et al, 2013;Tang et al, 2015), with mixed results.…”
Section: Do Pleiotropic Effects Underlie Sex-differences In Smokingmentioning
confidence: 99%
“…11 Power analyses were therefore performed for the SABPA study cohort. Using previous studies, ambulatory autonomic dysfunction 12 and cortisol data 13 , 14 were used to obtain relevant effect sizes based on differences in biological profiles and genotyping hypothalamic-pituitary-adrenal (HPA) axis variation. Resulting sample sizes of 50–416 would enable explanation of biological differences and detection of single nucleotide polymorphisms (SNPs) with a statistical power of 0.8, and level of significance of 0.05.…”
Section: Who Is In the Cohort?mentioning
confidence: 99%
“…A further investigation using the PROMO prediction tool (30) suggested that the locus of rs139753473 interacted with two transcription factors, including the glucocorticoid receptor alpha and the androgen receptor. Interestingly, the glucocorticoid receptor has been reported to be associated with the probability of smoking severity and cessation in a sample of obstructive airway disease patients (31). It has been suggested that cigarette smoking could increase androgen receptor activity (32).…”
Section: Bioinformatics Functional Assessment Of Rftn1mentioning
confidence: 99%